Private Capital Inflows and Stock Market Development: An Empirical Insight - Fredrick Ikpesu; Shiro A Abass (Universitas Kuningan, 2022)
Over the past years, countries have used private capital inflows to enhance and deepen the growth of their stock market. Using time-series data between 1981 to 2017, the study deployed the dynamic ordinary least square (DOLS) and Granger causality techniques to examine the effect of private capital inflows on stock market development and also the direction of causality. The study outcome revealed that FDI positively and significantly affects the development of stock market in the country. Besides, the study outcome also showed that portfolio investment has a positive link with the country stock market development. In addition, the study also showed that FDI Granger cause stock market development. Drawing from the outcome of the study, it is recommended that the government should continuously implement and improve policies that attract FDI into the country to enhance and deepen the nation’s stock market. Besides, the monetary policy needs to continuously improve policy on portfolio investment to tackle its inherent nature, which is volatile.